Experimental investigation of electromagnetic energy harvesting induced by sloshing motion - Amir Hossein Abdolmaleki; Mahdi Asadi; Meisam Farajollahi; Omid Malaie (Results in Engineering, 2025)
Global demand for energy and the need to mitigate the environmental impact of fossil fuels continue to grow. To tackle this issue, researchers have focused significant attention on clean and renewable energy sources. Energy harvesting systems offer a promising solution for sustainable power generation by capturing and converting ambient energy from various sources into usable electrical energy. Recently, several energy harvesting technologies have taken advantage of the sloshing phenomenon. However, most of these systems rely on piezoelectric or ferrofluid-based mechanisms, which often face limitations in cost-effectiveness, energy efficiency, or material constraints. This study presents a solution for harvesting energy from the sloshing of water in a tank and examines the influence of various parameters on its efficiency. In this system, a neodymium N42 solid magnet is placed on the surface of the water inside a coiled container. Several laboratory experiments are conducted under different conditions to measure the induced voltage. The measurements showed the highest open-circuit voltage and output power as 34 mV and 94.5 μW (at optimal load resistance), respectively. The system achieved a maximum output power density of 189 mW/m³, demonstrating a higher energy output compared to other systems in the literature. The simple design and efficient performance of this system under varying conditions make it adaptable for large-scale deployments in marine and coastal environments.